Youth citizenship at the end of primary school: the role of language ability. Issue 2 (15th March 2017) - Eidhof, Bram B. F.; ten Dam, Geert T. M.; Dijkstra, A. B.; van de Werfhorst, H. G.
Abstract: Schools are expected to fulfil different types of goals, including citizenship development. An important question is to what extent schools can simultaneously promote different learning outcomes. In this paper, we investigate the relationship between language ability and youth citizenship. Using a representative sample of 2429 grade 6 pupils (age 11–13) in 138 primary schools in the Netherlands, our findings confirm that language ability is strongly associated with pupils' youth citizenship outcomes, in particular with citizenship attitudes and knowledge. Contrary to popular belief, we conclude that stimulating pupils' language development need not compete with investing in pupils' citizenship development. Rather than a trade-off, our findings suggest a positive relationship between language ability and citizenship development.